Constitutionalism and public good (Reflection of political conflicts in the constitutional law) - Reza Taran (رهیافتهای سیاسی و بین المللی)
The constitution and its amendments showed the practical and intellectual conflict of the multiple social forces in the constitutional period. The purpose of writing this article was to understand this conflict based on the concept of public good and to find the effects, signs and results of this conflict in the constitution. How did the activists of the constitutional period perceive the concept of public good, and how was the conflict between the interpretations of public good reflected in the constitution? According to Skinner's methodology, Iran's defeat of Russia, Iranians' acquaintance with the new world, and the granting of privileges to foreigners met the grounds for the evolution of the concept of good. The authors of the texts pursue their purpose by presenting their interpretations of the concept of rejection, negation, and conflict with other actors . The findings show that the main conflict between the three social forces, including: intellectuals, pro-constitutional scholars and anti-constitutional scholars, and each received a public good from the perspective of social status and class interests, and each intended to include its own interpretation in the constitution. The result of this controversy was the division of the constitutional constitution into the good of the monarchy, the good of the Sharia and the good of the nation.